2023
DOI: 10.3390/su15139868
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Marketing Communication and Islamic Financial Literacy on Islamic Financial Inclusion and MSMEs Performance: Evidence from Halal Tourism in Indonesia

Abstract: The development of halal tourism in Indonesia is the focus of the Indonesian government and MSMEs have an important role in supporting the development of halal tourism in Indonesia. This study aims to examine the relationship between marketing communication and Islamic financial literacy on Islamic financial inclusion and MSME performance in the halal-tourism sector. A covariance-based SEM technique utilizing LISREL software was used to analyze the data from this investigation. Nonprobability sampling was empl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
1
4
0
3
Order By: Relevance
“…There is a positive and significant effect of financial inclusion on MSME performance, supporting previous studies yielding the same result (Mujiatun et al, 2023;Thathsaani & Jianguo, 2022). This study indicates that improved financial inclusion leads to enhanced business capital.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…There is a positive and significant effect of financial inclusion on MSME performance, supporting previous studies yielding the same result (Mujiatun et al, 2023;Thathsaani & Jianguo, 2022). This study indicates that improved financial inclusion leads to enhanced business capital.…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, a hypothesis was formulated for this research: H1: Financial literacy has a positive and significant effect on MSME performance mediated by venture capital Financial inclusion plays influential role in MSME performance (Thathsaani & Jianguo, 2022). Mujiatun et al (2023) found a positive and significant association between Islamic financial inclusion and business performance among halal-tourism entrepreneurs. Financial inclusion is linked to the performance of MSMEs, as it encourages individuals to access financial products, facilitating more unrestricted financial transactions (Efan et al, 2022).…”
Section: Hypotheses Developmentmentioning
confidence: 86%
“…Selain itu, integrasi antara perencanaan anggaran dan tujuan strategis institusi menjadi fokus penting dalam penelitian literatur, seperti yang diungkapkan oleh Mujiatun et al (2023). Penelitian ini menunjukkan bahwa institusi yang mampu mengintegrasikan perencanaan anggaran dengan visi, misi, dan tujuan strategisnya cenderung lebih sukses dalam mencapai pencapaian yang diinginkan.…”
Section: Tinjauan Pustakaunclassified
“…Integrasi antara perencanaan anggaran dengan visi, misi, dan tujuan strategis institusi menjadi kunci JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi) E-ISSN: 2579-5635, P-ISSN: 2460-5891 Volume 10 (2) April Tahun 2024, Hal 1032-1039 penting dalam mencapai keberhasilan. Penelitian literatur menunjukkan bahwa perguruan tinggi agama Islam yang berhasil mengintegrasikan perencanaan anggaran dengan tujuan-tujuan strategisnya cenderung lebih sukses dalam mencapai pencapaian yang diinginkan (Mujiatun et al, 2023).…”
Section: Faktor-faktor Yang Mempengaruhi Efektivitas Perencanaan Angg...unclassified
See 1 more Smart Citation